História social : a moda feminina através da imprensa (1950-1960) - Schütz, Augusta (2023)
The present dissertation aims to analyze the construction of women's fashion in the Brazilian press, taking as its object of study the periodical “Jornal das Moças” in the 1950s. To do so, a qualitative methodology is used through content analysis, in order to identify and understand the main trends and characteristics that guide the discourse on fashion present in the periodical. In this sense, the research contextualizes fashion, its historical origins and development in the modern world, highlighting its relevance as a cultural and social phenomenon, as well as delving into the analysis of the concepts and approaches of important sociologists who studied the subject, such as Thorstein Veblen (1857-1929), Georg Simmel (1858- 1918), and Pierre Bourdieu (1930-2002). The results show that women's fashion in the 1950s was marked by the emergence of new trends that sought to simultaneously affirm femininity and women's modernity. It was also possible to observe that “Jornal das Moças” played a fundamental role in the diffusion of these trends, being an important source for understanding the social transformations that occurred at that time. Finally, the dissertation concludes that women's fashion is a complex and multifaceted phenomenon that reflects the social, economic, and cultural dynamics of a particular era, and the analysis of periodicals such as “Jornal das Moças”, coupled with historical concepts and sociological approaches, can contribute to a broader and deeper understanding of fashion as a social phenomenon through the press.